RELATIONS BETWEEN ACTIVISTS AND CITIZENS, THE INTERNAL DRIVING FORCE OF THE SOCIAL MOVEMENT AS A FESTIVAL: A CASE STUDY OF THE 2016 – 2017 CANDLELIGHT VIGILS - LEE, Doo Hyeong (International Journal of Korean Humanities and Social Sciences, 2021)
The 2016-2017 candlelight vigil was a very important event because it led to the impeachment of an incumbent president for the first time in South Korea’s constitutional history. Above all, it was a remarkable phenomenon in that it unfolded peacefully and acted like a festival even though many citizens gathered on the streets to demand the president’s impeachment, which is essentially an extreme argument under institutional democracy. Violence, which was common in previous mass movements, was impossible in the 2016-2017. Some emphasized the heightened sense of citizenship, while others understand it in a historical context, but it does not see the dynamics of change that exist within the mass movement. Moreover, peaceful and festive gatherings have received a lot of attention, especially in the 2000s. And this is highlighted as a strategy for citizens who voluntarily come out on the street to keep their distance from activists. The existence of a movement dealing with various political agendas was seen as a risk of distorting the purpose of the manifestation. For citizens, distancing from them is an important strategy to preserve the purity of the movement. Therefore, the ‘flag’, which is a symbol of the movement, was excluded from the square. However, the so-called ‘Any Flag Festival’ that appeared at the 2016-2017 candlelight vigils bridges the gap between the movement represented by the flag and the general participants. The group play using flags relieved the tension between the movement’s organization and the citizens, which was an internal conflict factor in the manifestation, which coincidentally led them to be together. As a result, this formed an important social context for mass movements such as festivals, which became important in the 2000s, to be completed in 2016 and 2017.